ELDERLY EMPOWERMENT THROUGH ACTIVE PARTICIPATION IN INDEPENDENT FOOD BARN - Wiryanti Oetami, Sri; Anggraini, Bea; Handayani, Dwi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This community service is focused on empowering the elderly. Elderly empowerment is an effort to make the elderly active and responsive. Activities in self-sufficient food storage with a priority on vegetable farming are suitable for empowering the elderly. Planting activities while enjoying a fresh and green environment are light ways that can help relax and are safe for the elderly. This community service is carried out by socializing pot farming techniques, hydroponics, aquaponics, and vertical gardens. The method used is participatory education and socialization with material related to the provision of planting media, nurseries, planting, and management of vegetable products. Participants in this activity are elderly who are members of farmer groups. The result of the dedication is the realization of a vegetable garden, and the product can be sold to the elderly group in the Rungkut Barata residential area, Rungkut Menanggal Village, Gunung Anyar District, Surabaya. A vegetable garden in this environmental facility illustrates an urban agricultural 'oasis', which is expected to be a reference for optimal utilization of public facilities. In addition, activities can be a reference in empowering the elderly as active and responsive people towards their environment.